Gastrointestinal Stromal Tumor in the Cecum of a Horse. (19th July 2012) - Stephan, S.; Hug, S.; Hilbe, M.
Abstract : Gastrointestinal stromal tumors (GISTs) are defined as specific CD117-(Kit, stem cell factor receptor) expressing tumors of the gastrointestinal (GI) tract. They are believed to originate from the interstitial pacemaker cells of Cajal (ICC) or their progenitor cells. In horses only a few cases of GISTs are described in the literature. In the present paper the macroscopical, histological, immunohistochemical, and ultrastructural features of an equine cecal GIST are described.